VARIANT ANATOMY OF THE BRACHIAL PLEXUS - A.A. SUFIANOV; R.KH. SAGDIEV; V.S. SORIN; V.A. PITEROV (Avicenna Tajik State Medical University, 2022)
The brachial plexus (BP) is a complex of nerve structures arising from the ventral rami of the lower four cervical (C5-C8) and upper thoracic (Th1) spinal nerves. The number of described variants of BP has been increasing every decade. This paper analyzes the world literature data on the anatomy of the BP. The sources of information used included: PubMed, Web of Science, Scopus, MEDLINE, EMBASE, Biosis Citation Index, SciELO Citation Index, RSCI data bases. It was noted that the anatomy of the BP is variable, its "classic" variant of the structure occurs in less than 50% of cases. In other cases, there were significant differences in structure and course from the "classic" version.